2022
DOI: 10.4103/jomfp.jomfp_341_21
|View full text |Cite
|
Sign up to set email alerts
|

Forensic genetics

Abstract: Forensic science corresponds to the employment of science to the law or legal matters. One of the major concerns of legal system is to deduce the recognition of an item or individual, involved in crime for which forensic expert plays a pivotal role. Forensic odontology, a budding branch in dentistry, involves the application of dentistry to the legal system. The dental characteristics are considered as one of the primary characteristics of identification as per Interpol DVI guidelines. Thus, establishing the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
3
1
Order By: Relevance
“…Contrarily, Malik et al (2022) reported that using biochemical or genetic records for age estimation was gaining acceptance among professionals, conflicting with our survey findings where the participants expressed difficulties using these records [ 38 ]. This discrepancy may be due to varying levels of access to and proficiency with advanced biochemical and genetic techniques among professionals.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…Contrarily, Malik et al (2022) reported that using biochemical or genetic records for age estimation was gaining acceptance among professionals, conflicting with our survey findings where the participants expressed difficulties using these records [ 38 ]. This discrepancy may be due to varying levels of access to and proficiency with advanced biochemical and genetic techniques among professionals.…”
Section: Discussioncontrasting
confidence: 92%
“…Alterations due to toothburn have been extensively documented in the literature [ 43 , 44 ]. These studies have shown that even minute teeth fragments can be identified amongst burn residues [ 38 ]. Moreover, they have provided a reliable methodology to estimate the exposure temperature, demonstrating that there may be no or minimal anatomical changes from such exposure.…”
Section: Discussionmentioning
confidence: 99%
“…In forensics, gender identification plays a crucial role in personal identification. While morphological traits are effective in identifying genders, their application is compromised in mutilated human remains or when only fragments of the body are recovered [ 1 ]. In such situations, Forensic odontologists can help particularly when only a few teeth and skull remain are available.…”
Section: Introductionmentioning
confidence: 99%
“…OPT also allows the workup of orthodontic therapy through the assessment of dental and skeletal relationships, crowding investigation, and the identification of missing or extra teeth [1][2][3]. Moreover, OPTs are routinely used to assess bone age [4] and for forensic purposes [5].…”
Section: Introductionmentioning
confidence: 99%